Exploring The Experiences of The BSED Major in Science Students in The Use of Laboratory Facilities and Equipment - Kimberly Hiyan; Jehanne Ortega; Glowy Leigh Algara; Daisy Catubig; Alfer Jann Tantog; Genesis Naparan (Journal of Elementary and Secondary School, 2025)
Laboratory facilities and equipment are essential in science education, providing students with hands-on experience that enhances their scientific inquiry and critical thinking. However, many students face challenges due to outdated equipment, insufficient resources, and inadequate technical support, all of which hinder effective experimentation and learning. These limitations negatively impact students' academic performance and preparedness for future scientific endeavors. This qualitative study investigates the challenges BSED science majors encounter in laboratory-based learning at a private higher education institution in Pagadian City during the 2023-2024 academic year. Using Sharan B. Merriam’s case study model, the research explores how limited laboratory access and resource constraints affect students' learning experiences. Data was collected through interviews and observations, with purposive sampling ensuring that participants met specific criteria. Thematic analysis and triangulation identified key themes, including laboratory accessibility, resource utilization, challenges in conducting experiments, and student coping strategies. Findings reveal that students struggle with inadequate laboratory spaces, malfunctioning or outdated equipment, and a lack of technical guidance, all of which impede their academic development. These issues underscore the crucial need for enhanced laboratory facilities and instructor training to facilitate effective science instruction. The study recommends enhancing laboratory infrastructure, ensuring regular equipment maintenance, and providing students and educators with adequate training in laboratory operations. Strengthening faculty expertise in handling laboratory tools is also essential. Addressing these concerns will contribute to a more effective science education framework, promoting better learning outcomes and higher standards of scientific experimentation.